Simultaneous Gas Chromatography-Mass Spectrometry Quantification of Endogenous [(12)C]- and Applied [(13)C]Indole-3yl-Acetic Acid Levels in Growing Maize Roots - Meuwly, Philippe (1991)
The use of stable indole-3yl-acetic acid (IAA) labeled by 6 atoms of (13)C allowed, after [(13)C]IAA treatment, simultaneous gas chromatography-mass spectrometry quantifications of both endogenous [(12)C]IAA and applied [(13)C]IAA levels in Zea mays L. roots. Root material was immersed for 1 hour in a buffered (pH 6.0) solution without or with [(13)C]IAA at 10(−7) molar. Both applied and endogenous IAA were thus measured for three zones of the roots (apical, elongating, differentiating) directly after treatment and also 2 hours later. Growth was followed over a 4 hour period. Roots not immersed elongated more than control roots (immersed in buffer), which grew more than IAA-treated roots. Immersion in buffer induced a large decrease (−68%) of [(12)C]IAA in the apical part of control roots, whereas immersion in [(13)C]IAA prevented most of it. No significant difference between control and treated roots occurred in the two other zones. Two hours after treatment, [(13)C]IAA had completely disappeared from the elongating zone even though [(12)C]IAA level was essentially stable. A direct relationship occurred between the level of IAA in the elongating zone and the growth of the root. This relationship was strongly disturbed if unmetabolized [(13)C]IAA was present. However, the relationship returned to its initial state when significant amounts of free [(13)C]IAA were no longer detectable. These results are discussed in terms of the stability of both types of compounds and the utility of the method of using stable isotopes of hormones, for the understanding of hormonal regulation of plant growth.